You can conquer cancer : a new way of living - Gawler, Ian (Tarcher/Penguin, a member of Penguin Group (USA), 2015)
"Tarcher's updated edition of an international, perennial bestseller-with more than 250,000 copies sold worldwide. As a young veterinarian and decathlon athlete, Dr. Ian Gawler had his right leg amputated as a result of bone cancer in 1975. The cancer returned later that year. Against almost impossible odds, he recovered and went on to found one of the world's first lifestyle-based cancer self-help and support programs in 1981. Originally published in 1984, You Can Conquer Cancer is a revolutionary book that has sold hundreds of thousands of copies worldwide and has been translated into fourteen languages. This edition is completely updated and contains whole sections that provide important new information and self-help techniques. Notable for its clarity, this book expands upon what is a truly integrated, holistic approach to cancer-emphasizing nutrition, the power of the mind, meditation, family and social support, and the spiritual dimension of life"--